Design and Analysis of Distributed Embedded Systems IFIP 17th World Computer Congress - TC10 Stream on Distributed and Parallel Embedded Systems (DIPES 2002) August 25–29, 2002, Montréal, Québec, Canada - Kleinjohann, Bernd; Kim, K.H. (Kane); Kleinjohann, Lisa; Rettberg, Achim (Springer US, 2002)
Design and Analysis of Distributed Embedded Systems is organized similar to the conference. Chapters 1 and 2 deal with specification methods and their analysis while Chapter 6 concentrates on timing and performance analysis. Chapter 3 describes approaches to system verification at different levels of abstraction. Chapter 4 deals with fault tolerance and detection. Middleware and software reuse aspects are treated in Chapter 5. Chapters 7 and 8 concentrate on the distribution related topics such as partitioning, scheduling and communication. The book closes with a chapter on design methods and frameworks
Keywords: Computer-Aided Engineering (CAD, CAE) and Design; Computer Communication Networks; Processor Architectures; Computer-aided engineering; Computer communication systems; Microprocessors; Eingebettetes System; Verteiltes System; Konferenzschrift -- 2002 -- Montreal